2010
DOI: 10.1007/s12282-010-0223-8
|View full text |Cite
|
Sign up to set email alerts
|

Mammography and ultrasound features of triple-negative breast cancer

Abstract: Mammography and ultrasound imaging together revealed that the morphological features of triple-negative breast cancer include a lobulated mass, with less attenuating posterior echoes, some vascularity, and low elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 11 publications
11
41
3
Order By: Relevance
“…This study showed that approximately 80% of TNBC patients had a visible tumour mass on mammography, and the masses were less frequently associated with microcalcification. This finding is consistent with previous studies [20][21][22][23][24][25][26] that observed TNBC was most commonly presented as a mass (58.2-100%), and the mass was less frequently associated with microcalcifications (4.7-29%). Our data showed that the shape of TNBC lesions was more likely to be round/oval (58.1%), which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that approximately 80% of TNBC patients had a visible tumour mass on mammography, and the masses were less frequently associated with microcalcification. This finding is consistent with previous studies [20][21][22][23][24][25][26] that observed TNBC was most commonly presented as a mass (58.2-100%), and the mass was less frequently associated with microcalcifications (4.7-29%). Our data showed that the shape of TNBC lesions was more likely to be round/oval (58.1%), which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, TNBC is likely to manifest benign morphological features. Moreover, this study revealed that on mammography TNBC was less frequently associated with calcifications (total calcification: 25.9%, only calcification: 5.6%), which was consistent with other studies [20][21][22][23][24][25][26] (total calcification: 11.7%-36%, only calcification: 0%-13.6%). Yang et al 20 indicated that the relative low levels of calcification in TNBC were consistent with the low incidence of ductal carcinoma in situ in TNBC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, 67.7% of TN cancers were seen as round, oval, or lobulated masses, compared with 70% [10] to 75% [11] in previously reports. We found circumscribed margins in the TN lesions less often than was described in other studies [10.8% vs. 24% [4] to 43% [11]. In our study, circumscribed margins occurred in similar rates in TN and HR-positive/HER-2-negative tumors .…”
Section: Mammographysupporting
confidence: 55%
“…Additionally, the presence of shadowing was strongly associated with low grade (about 92% were low grade in their study). Kojima et al (17) mentioned that triple-negative breast cancers were more likely to be lobulated in shape and having circumscribed margins and less likely to show posterior attenuating. Our results confirm the findings of these studies.…”
Section: Discussionmentioning
confidence: 99%